1986
DOI: 10.1111/j.2042-3306.1986.tb03694.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vitamin E and selenium supplement on antibody production in horses

Abstract: Summary Fifteen horses used for serum production were maintained on low vitamin E and selenium diets. They were divided into four groups receiving: Group 1 no supplements, Group 2 vitamin E, Group 3 selenium and Group 4 both vitamin E and selenium. The humoral immune response to novel antigens, such as tetanus toxoid and equine influenza virus, was increased in groups receiving either vitamin E or selenium/vitamin E. No effects were recorded on the titres against Escherichia coli or the levels of immunoglobuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 12 publications
1
11
0
3
Order By: Relevance
“…This may relate to the longer period of time that the LS horses had received a low-Se diet at the time of this vaccine challenge (approximately 14 mo when aeeounting for initial depletion phase), compared with the previously reported study where the vaccine challenge was administered after 7 mo on the low-Se diet (Brummer et al, 2011). This may indicate an adaptation to the lower dietary Se intake, possibly through eompensation by other eomponents of the antioxidant system, such as vitamin E. Similar to the eurrent study, Baalsrud and Ovemes (1986) reported comparable antibody production in response to vaccination between horses on a Se-supplemented (0.5 mg Se/kg DM) or a low-Se and low-vitamin E control diet (0.03 mg Se/kg DM, 18 mg a-tocopheryl acetate/kg DM). However, horses receiving a combination of Se and vitamin E supplementation (0.5 mg/kg DM, 80 mg a-tocopheryl acetate/kg DM) reportedly had improved antibody production compared with the low-Se and vitamin E control group (Baalsrud and Ovemes, 1986).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This may relate to the longer period of time that the LS horses had received a low-Se diet at the time of this vaccine challenge (approximately 14 mo when aeeounting for initial depletion phase), compared with the previously reported study where the vaccine challenge was administered after 7 mo on the low-Se diet (Brummer et al, 2011). This may indicate an adaptation to the lower dietary Se intake, possibly through eompensation by other eomponents of the antioxidant system, such as vitamin E. Similar to the eurrent study, Baalsrud and Ovemes (1986) reported comparable antibody production in response to vaccination between horses on a Se-supplemented (0.5 mg Se/kg DM) or a low-Se and low-vitamin E control diet (0.03 mg Se/kg DM, 18 mg a-tocopheryl acetate/kg DM). However, horses receiving a combination of Se and vitamin E supplementation (0.5 mg/kg DM, 80 mg a-tocopheryl acetate/kg DM) reportedly had improved antibody production compared with the low-Se and vitamin E control group (Baalsrud and Ovemes, 1986).…”
Section: Discussionsupporting
confidence: 51%
“…This may indicate an adaptation to the lower dietary Se intake, possibly through eompensation by other eomponents of the antioxidant system, such as vitamin E. Similar to the eurrent study, Baalsrud and Ovemes (1986) reported comparable antibody production in response to vaccination between horses on a Se-supplemented (0.5 mg Se/kg DM) or a low-Se and low-vitamin E control diet (0.03 mg Se/kg DM, 18 mg a-tocopheryl acetate/kg DM). However, horses receiving a combination of Se and vitamin E supplementation (0.5 mg/kg DM, 80 mg a-tocopheryl acetate/kg DM) reportedly had improved antibody production compared with the low-Se and vitamin E control group (Baalsrud and Ovemes, 1986). Therefore, it is plausible that the adequate vitamin E status of our horses allowed for a normal antibody response to vaccination, even in the horses of low Se status.…”
Section: Discussionmentioning
confidence: 59%
“…at most, 42 iu/kg DM. However, higher concentrations !ly different, P c 0.05 may be required to ensure immunocompetence (Baalsrud and Overnes 1986;NRC 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In horses fed diets low in vitamin E and selenium, the role of α‐tocopherol in the humoral immune response was demonstrated by vaccination against tetanus toxoid and equine influenza virus . An increased IgG response occurred in horses receiving either vitamin E or vitamin E and selenium.…”
Section: Chemical Structure and Propertiesmentioning
confidence: 99%